Ironie et jeux de mots au Québec: enjeux socio-culturels - Molinari, Chiara (Ponti/Ponts, 2021)
This article aims to explore the relationship between irony and puns produced in Quebec and the respective socio-cultural context. Starting from the assumption that the strategies put in place to create puns and to produce ironic effects are the same in the different varieties of French, it seemed relevant to focus on the relationship between puns and irony, on the one hand, and linguistic awareness, on the other. To this end, the study will explore - through a methodology that combines lexicology and discourse analysis - a corpus made up of sketches by the humorist Boucar Diouf and blog posts from Mots et maux de la politique by the journalist Antoine Robitaille. Given the surconscience linguistique that characterises Québécois humourists, the investigation will try to prove that their texts (be they oral or written) go beyond the epilinguistic dimension and are instead closer to the metalinguistic one.